Zad . 11 / 40

a) -2:(7-11)
b) 6-(-7) x (-2) : -4
c) (-2- 4) x (-6) : (-3) do potęgi 2
d) (-3) x (-2 -10) - 5 : 7-9
e) (-2) do potęgi 3 + 45 :( - 3 do potęgi 2 )
f) 15 - ( - 2) x 4 : - 11 + 4 + 5-2:2-3
g) (-2) x 1-4 : 4
h) 12-20 : 2 x 3
i) -8+4 : 3 x 6 : -1+3




x - znak mnożenia
tam gdzie pisze do potęgi 3 i 2 , to chodzi o tą 3 i 2 na górze.



Proszę o szybkie rozwiązaniee !

3

Odpowiedzi

2010-03-02T18:27:51+01:00
a -2 : (-4 )=0,5
b 6+7* 0,5= 6+3,5=9,5
c -6*(-6):(-27)=36 : (-27)=1,333333..
e -8+45:6=-8+7,5=0,5
(-3) x (-2 -10) - 5 : 7-9= (-3) x (-8) -5 : (-2) = 24 +10 = 34
g (-2) x 1-4 : 4=-2-1=-3
h 12-20 : 2 x 3=12-10*3=12-30=-1
2 1 2
Najlepsza Odpowiedź!
2010-03-02T18:28:37+01:00
A) -2:(7-11) = -2 : -4 = 2

b) 6-(-7) x (-2) : -4 =
=6- 14: (-4) = 6 + 3,5 = 9,5

c) (-2- 4) x (-6) : (-3) do potęgi 2
= (-6) x (-6) : 9 = 36 : 9 = 4

d) (-3) x (-2 -10) - 5 : 7-9=
= (-3) x (-8) -5 : (-2) =
= 24 +10 = 34

e) (-2) do potęgi 3 + 45 :( - 3 do potęgi 2 )=
= -8 + 45 : 9 = -8 + 5 = -3

f) 15 - ( - 2) x 4 : - 11 + 4 + 5-2:2-3
=15+ 8 : (-11) +9-1-3 = 15 - ⁸/₁₁ +5 = 20 - ⁸/₁₁ = 19 ³/₁₁

g) (-2) x 1-4 : 4=
= -2 -1 = -3

h) 12-20 : 2 x 3=
=12-10 x 3 = 12-30 = -18

i) -8+4 : 3 x 6 : -1+3 =
= -8 + ⁴/₃ x -6 +3 = -8 - 8+3 = -16+3 = -13
2010-03-02T18:29:54+01:00
A) -2:(7-11)
-2:-4=0.5
b) 6-(-7) x (-2) : -4
6+7 *0.5=7.5
c) (-2- 4) x (-6) : (-3) do potęgi 2
-6*-6:-9=-6*1/3=-2
d) (-3) x (-2 -10) - 5 : 7-9
-3*-12-5:2=-3*-12-2.5=48-2.5=45.5
e) (-2) do potęgi 3 + 45 :( - 3 do potęgi 2 )
-8+45:6=-8+7.5=-0.5
f) 15 - ( - 2) x 4 : - 11 + 4 + 5-2:2-3
17*4:-11+4+5-1-3=17*

g) (-2) x 1-4 : 4
-2*1-1=-2*0=0
h) 12-20 : 2 x 3
12-10*3=12-30=-18
i) -8+4 : 3 x 6 : -1+3
-8+4/3*6:-1+3=-8+8:-1+3=-8-8+3=-13
3 2 3